Humanization of Islamic Education in the Perspective of Contemporary Social Theory - Latifah; Masdar Hilmy; Desi Erawati (Yayasan Pendidikan Tanggui Baimbaian, 2026)
The humanization of education is an important agenda in the development of Islamic education amid the dynamics of modern social life. Islamic education does not merely function as a process of transmitting religious knowledge, but also as a means of shaping complete human beings who possess dignity and social awareness. This article aims to analyze the concept of the humanization of Islamic education from the perspective of contemporary social theory and its relevance to current educational practices. This study employs a qualitative approach using a library research method by examining various literature related to Islamic education, social theory, and modern educational thought. The results of the study indicate that the humanization of Islamic education is aligned with several contemporary social theories, such as humanistic theory, social constructivism theory, and critical theory in education. Fundamental values in Islam such as justice, compassion, equality, and respect for human dignity serve as essential foundations in building a humanistic educational paradigm. In the context of modern education, the humanization approach can be realized through dialogical learning, strengthening the values of empathy, and developing students’ social awareness. Therefore, the integration of Islamic educational principles and contemporary social theory can serve as a strategic foundation in building an educational system that is not only oriented toward cognitive aspects but also toward character formation and humanitarian awareness.